Evaluation by experts and designated users on the learning strategy using sketchup make for elevating visual spatial skills and geometry thinking - Wahab, R. A. (BOLEMA Departamento de Matematica, 2017)
The teaching and learning of Geometry should be meaningful and not merely reacting to the teacher's stimuli. Hence, students should be given opportunities to experiment when learning mathematics through exploration and investigation of geometric shapes by themselves. For that reason, a Learning Strategy for 3-dimensional Geometry using the SketchUp Make dynamic software, called LSPE-SUM was designed through a step-by-step instruction to help students to improve their visual spatial skills and geometric thinking. Visual spatial skills were carefully integrated onto each van Hiele levels of Geometry thinking through specific arrangement of specially crafted learning activities. Such arrangement was vital to ensure that students could achieve better cognitive enhancement in visual spatial skills by communicating and interacting physically and socially according to the hierarchical van Hiele model of Geometry thinking. LSPE-SUM capitalized the dynamic features of SketchUp Make to facilitate the elevation of visual spatial skills and Geometry thinking during the learning processes. The whole process of designing and developing the LSPE-SUM adopted the five cyclic stages of ADDIE instructional design model. The purpose of this article was to report the details of the final two stages, more specifically, implementation and evaluation of LSPE-SUM. This learning strategy was tried out twice upon twelve different students in a classroom setting over a period of 3 weeks each. Besides that, LSPE-SUM was also given to experts to obtain their views and evaluation on its functionality. Quantitative and qualitative approaches were used to collect data as well as to analyze the experts and students' views on the suitability of LSPE-SUM. Analysis of students' views suggested that LSPE-SUM has assisted most of them in elevating both their visual spatial skills and Geometry thinking; while, all experts claimed that LSPE-SUM was pedagogically functional and served its purposes well.